2019
DOI: 10.6018/cpd.372381
|View full text |Cite
|
Sign up to set email alerts
|

Estilo de interacción del entrenador, clima motivacional percibido y satisfacción de las necesidades psicológicas básicas en futbolistas jóvenes

Abstract: El objetivo del presente trabajo fue analizar el clima motivacional percibido a través de las relaciones existentes entre el estilo de interacción del entrenador (apoyo a la autonomía o estilo controlador) con los constructos de la Teoría de las Metas de Logro (ego o tarea) y el grado de satisfacción con las necesidades psicológicas básicas en una muestra de jóvenes deportistas. Participaron 125 futbolistas de la provincia de Málaga (España), con edades comprendidas entre los 15 y 18 años (M= 16.66, DT= 1.13).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
1
6
0
5
Order By: Relevance
“…In line with previous studies [19][20][21], we hypothesised that players' perceived autonomy support would predict both BPN frustration and satisfaction, and the latter would predict their sport commitment. Yet, given the disparity of previous results in youth soccer players [25,26], the relationship of the four controlling behaviours (i.e., controlling use of rewards, negative conditional regard, intimidation, and excessive personal control) with BPN satisfaction and frustration was not specifically hypothesised. Nevertheless, we expected that athletes' BPN frustration would negatively predict sport commitment (Figure 1).…”
Section: The Present Studymentioning
confidence: 83%
See 1 more Smart Citation
“…In line with previous studies [19][20][21], we hypothesised that players' perceived autonomy support would predict both BPN frustration and satisfaction, and the latter would predict their sport commitment. Yet, given the disparity of previous results in youth soccer players [25,26], the relationship of the four controlling behaviours (i.e., controlling use of rewards, negative conditional regard, intimidation, and excessive personal control) with BPN satisfaction and frustration was not specifically hypothesised. Nevertheless, we expected that athletes' BPN frustration would negatively predict sport commitment (Figure 1).…”
Section: The Present Studymentioning
confidence: 83%
“…However, there are a limited number of studies that have examined the relationship of the four controlling coach behaviours with BPN satisfaction and frustration, especially in youth soccer players. A study [25] with U-15 and U-18 soccer players indicated that all four controlling behaviours were negatively associated with relatedness and competence satisfaction, with the exception of negative conditional regard in the need for competence. However, no controlling behaviour was related to autonomy satisfaction in that study.…”
Section: Introductionmentioning
confidence: 98%
“…De facto, nos últimos anos, temos vindo a assistir a uma proliferação dos estudos com base na SDT, no domínio da atividade física, nomeadamente: no desporto (e.g. Álvarez, Castillo, Duda, & Balaguer, 2009;Gagné, Ryan, & Bargmann, 2003;Luque et al, 2019;Monteiro et al 2018a;Monteiro, Pelletier, Moutão, & Cid, 2018b;Monteiro et al, 2019;Reinboth & Duda, 2006), no exercício (e.g. Edmunds, Ntoumanis, & Duda, 2006, 2008Hagger & Chatzisarantis, 2008;Markland & Tobin, 2010;Rodrigues et al, 2018;Rodrigues et al, 2019;Rodrigues et al, 2020) e na educação física (e.g.…”
Section: Quadro Conceptualunclassified
“…Es por estas razones, por las que diferentes disciplinas empíricas han realizado estudios enfocados en el desarrollo y maximización del rendimiento futbolístico; centrándose en la identificación de los factores que tienen un mayor protagonismo en la explicación de la competencia o excelencia individual y colectiva en este deporte, donde se destaca, con gran consenso en la comunidad científica, el factor táctico-estratégico como el más determinante. De hecho, detrás de la práctica del fútbol se localizan múltiples beneficios en los procesos cognitivos relacionados con las funciones ejecutivas, como, por ejemplo, un aumento de la atención, control inhibitorio y memoria de trabajo (Moreno-Luque, et al, 2019).…”
Section: Introducción Y Estado De La Cuestiónunclassified
“…Más específicamente, en la evaluación del rendimiento en jugadores de fútbol, realizada por González, Campos y Romero (2014) se han encontrado resultados relacionados con las funciones ejecutivas, de modo que en atención-concentración, más de la mitad de los jugadores no pierde la concentración ante las decisiones arbitrales, ni tampoco ante los comentarios o gestos del entrenador. Finalmente, aunque son muchos los estudios que avalan la relación entre FEs y el rendimiento deportivo, ya que están directamente relacionadas con el éxito en el deporte (Alarcón, et al, 2017a;Hernández-Mendo, et al, 2019), el debate sigue abierto, pues presenta algunas controversias al respecto.…”
Section: Introducción Y Estado De La Cuestiónunclassified